Basic principles underlying racing dives - Rushall, B. S. (2000)
Dives are important in racing. Author lists the features of a "proper dive" and explains why other features leed to poorer starts. Conclusion concerning the question "Grap start or track start?" : What is the best foot placement on the blocks? A recent study has shown that a track start is better than a grab start (Juergens, Rose, Smith, & Calder, 1999). Previous research has not been definitive on this topic because swimmers are best at the start they have practiced most. When teaching new or developing swimmers to start, the track start is preferred to the double-leg or "grab" start. If a swimmer wants to change from a grab start, introduce the track start as soon as possible and practice it more than usual so that it will become the dominant movement pattern for starting.